Diagnosis of ocular disease in Ibadan by ultrasound (1995)
15 patients with ocular disease, in whom views of posterior segment of the eyes could not be obtained underwent ultrasonography of the eyes to aid in the diagnosis and further management of the patients. In some cases the ultrasound was then compared with the histological diagnosis when the eye was removed and in other cases to the ophthalmoscopic examination when a better view of the posterior segment could be obtained. This was done as a pilot study to ascertain the level of accuracy of our ultrasonic diagnosis and how much it could be depended upon for the very important decision of removal of the eye when indicated.